Clostridium butyricum Helps to Alleviate Inflammation in Weaned Piglets Challenged With Enterotoxigenic Escherichia coli K88 - Li, Haihua; Liu, Xuejiao; Shang, Zhiyuan; Qiao, Jiayun (Frontiers in Veterinary Science, 2021)
Background: Whether the probiotic Clostridium butyricum (CB) alleviates enterotoxigenic Escherichia coli (ETEC) K88-induced inflammation by regulating the activation of the toll-like receptor (TLR) signaling pathway is not clear, thus, we carried out this study. A total of 72 piglets (average body weight 7.09 ± 0.2 kg) were randomly divided into three groups of 24 piglets per group. Pigs were either fed a daily diet (NC, negative control), a diet tested every day by 1 × 109 CFU/mL ETEC K88 (PC, positive control), or a basal diet supplemented with 5 × 105 CFU/g CB and challenged with ETEC K88 (PC + CB group). Results: Our results showed that CB pretreatment attenuated the effect of ETEC K88 by decreasing C-reactive protein (CRP), which resulted in tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) production. Histological examination revealed that CB pretreatment alleviated intestinal villi injury caused by ETEC K88 challenge. Furthermore, CB pretreatment promoted mRNA expression of the negative regulators of TLR signaling, including myeloid differentiation factor (MyD88), toll-interacting protein (Tollip), and B cell CLL/lymphoma 3 (Bcl-3), in the intestines of ETEC K88-challenged piglets. ETEC K88-induced activation of nuclear factor kappa B (NF-κB) and nuclear factor of kappa light polypeptide gene enhancer in B cells inhibitor alpha (IκBα) was attenuated by CB pretreatment. Conclusion: These findings indicate that CB helps to maintain and strengthen the shape of intestinal villi and limits detrimental inflammatory responses, partly by inhibiting toll-like receptor 2 (TLR-2), toll-like receptor 4 (TLR-4), and toll-like receptor 5 (TLR-5) expression and inhibiting NF-κB p65, and promoting IκBα activation and synergism among its negative regulators.